ABM Proceedings 2018
DOI: 10.5151/2594-357x-31180
|View full text |Cite
|
Sign up to set email alerts
|

Utilização De Biomassa De Eucalipto Na Produção De Coque Metalúrgico

Abstract: Resumo A fim de investigar o consumo de biomassas, estudou-se sua participação na mistura base utilizada para a produção de Coque Metalúrgico, substituindo-a em 2% e 5% por madeira e serragem.Foram realizados enfornamentosem duplicata na unidade piloto de coque da Gerdau Ouro Branco com a caracterização de ensaios de reatividade (CRI), resistência após reação com CO 2 (CSR), Drum index (DI) e granulometria do coque produzido. A inserção da madeira mostrou-se mais viável do que a adição do mesmo nível de serrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…Figure 6: Ash behavior with biomass addition (Silva, 2016). This behavior is expected since the ash contents of biomasses tend to be much lower than coals used in coke mixtures.…”
Section: C) Influence Of Biomass Addition In Coal Mixtures For Cokemakingmentioning
confidence: 89%
See 3 more Smart Citations
“…Figure 6: Ash behavior with biomass addition (Silva, 2016). This behavior is expected since the ash contents of biomasses tend to be much lower than coals used in coke mixtures.…”
Section: C) Influence Of Biomass Addition In Coal Mixtures For Cokemakingmentioning
confidence: 89%
“…In figure 3 is possible to see a research using charcoal with different particle sizes. (Silva, 2016a) The drop in DI can be attributed to the increase in the inert content of the mixture, decreasing its coking power. According to Kubota (2008), the greater participation of aggregates above 1.5mm increases the concentration and propagation of cracks, depreciating the mechanical resistance of the coke.…”
Section: C) Influence Of Biomass Addition In Coal Mixtures For Cokemakingmentioning
confidence: 99%
See 2 more Smart Citations
“…But, as the present amount of Sulfur is very large there is still more of this element when compared to the BB in addition of 3, 5 and 10% of MT and LT [7]. Increase of Sulfur in coke demands actions to increase the desulphurization at the blast furnace and/or increase in the consumption of desulphurizing agents at the steel plant, so the costs of the production chain must be studied [8]. It can be observed that fluidity increases about 30 ddpm for every 1% of small tire added.…”
Section: Ash Sulfur and Fluiditymentioning
confidence: 99%